Keterpenjaraan perempuan dalam ruang kota di dalam "Lost in translation" (2003) dan "The good girl" (2002) - Saraswati, Asri (Wacana, Journal of the Humanities of Indonesia, 2009)
The urban space offers more challenges to the female self. Two motion pictures, Lost in translation (2003) and The good girl (2002), depict the issue of gender and space by conveying the city as prison for the female characters. This article analyses the urban space and argues that in the two movies, the female characters struggle and eventually create meaning in the urban room. Applying feminism and urban geography in analysing the position of female characters within the city, the paper finds that the two films offer their perception on, and solutions to, the imprisonment of women by the urban environment which is stereotypically masculine.